PENGARUH PEMBERIAN BERBAGAI JENIS PUPUK ORGANIK TERHADAP PERTUMBUHAN KANGKUNG DARAT (Ipomea reptans Poir.) - Rara Annisa Diniyah; Sri Wulandari; Suwondo Suwondo (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study aims to determine the effect of various types of organic fertilizers on the growth of water spinach (Ipomea reptans Poir.). This research is an experimental research conducted in October-December 2021 at the Biology Education Nature Laboratory, University of Riau. This study used a randomized block design consisting of 4 treatments with 4 groups of replications so that there were 16 experimental units. The treatment consisted of control treatment, manure treatment, bokashi fertilizer treatment, and composter drum fertilizer treatment. Data was collected by measuring plant height, number of leaves, and plant wet weight. The results showed that the application of various types of organic fertilizers had a significant effect on the growth of water spinach (Ipomea reptans Poir.). Bokashi fertilizer produced the best growth with a height of 37.80 cm, a total of 23.25 leaves, and a wet weight of 21.74 grams.Key Words: Organic fertilizer, Growth, Ipomea reptans Poir.